The Predictive Value of Multiple Electrode Platelet Aggregometry (Multiplate) in Adult Cardiac Surgery - Schimmer, Christoph; Hamouda, Khaled; Sommer, Sebastian Patrick; Özkur, Mehmet; Hain, Johannes; Leyh, Rainer (The Thoracic and Cardiovascular Surgeon, 2013)
Background The purpose of this retrospective observational study is to analyze the value of multiple electrode platelet aggregometry (Multiplate analyzer, Verum Diagnostica, Munich) as a point-of-care (POC) device in adult cardiac surgical patients.Methods Two hundred and twenty-three cardiac surgical patients were analyzed preoperatively and postoperatively with multiple electrode platelet aggregometry by stimulation ADPtest, ASPItest, and TRAPtest. End points were postoperative bleeding, need for reexploration, and perioperative transfusions requirements. Furthermore, a literature survey using the key phrases “platelet function” and “cardiac surgery” was performed.Results When comparing patients with normal Multiplate test results concerning end points, patients with pathological ADPtest (n = 140) needed significant more platelet concentrates (PCs) (p = 0.009), patients with pathological ASPItest (n = 175) did not show any significant differences, and patients with pathological TRAPtest (n = 139) needed more red blood cells (p = 0.008) and PCs (p = 0.02). The literature survey showed 208 hits, spanning the publication years 2002 to 2012 resulted in 123 hits.Conclusions The ADPtest and the TRAPtest significantly predict the requirement of perioperative blood transfusion. Therefore, multiple electrode platelet aggregometry is beneficial for POC testing in cardiac surgical patients. Prospective, randomized, and controlled clinical studies are rare.
Keywords: multiple electrode platelet aggregometry; cardiac surgery; POC testing; impedance aggregometry; platelet function analysis